Effect of eccentric isokinetic exercise on muscle strength and functional recovery after anterior cruciate ligament reconstruction - Michael Tim-Yun Ong; Jessica Sum-Yu Chan; Gene Chi-Wai Man; Jihong Qiu; Xin He; Qianwen Wang; Patrick Shu-Hang Yung (Elsevier, 2024)
Background: Previous studies have shown isokinetic exercise forms an important part in reconditioning the patients after anterior cruciate ligament reconstruction (ACLR) in regaining muscle strength and knee function. Although eccentric isokinetic training has been shown to enhance quadriceps muscle strength, the application toward benefiting patients after ACLR remains controversial. The present study aims to investigate the benefits of eccentric over concentric isokinetic exercises on knee muscle strength and its value in later stage of rehabilitation, including the return-to-sport. Methods: Thirty-six patients who had undergone ACLR for 4-to-6 months were assigned to receive either eccentric or concentric isokinetic training weekly for six weeks on top of their standardized post-operative exercise programme. The assessments include isokinetic test on the peak torques of quadriceps and hamstrings, single-leg hop test and ability to return-to-sport. Results: Both groups demonstrated significant gains on peak torques in quadriceps and hamstrings after training. At post-intervention, the peak torques for both quadriceps (p = 0.005) and hamstrings (p = 0.017) of the ACL-reconstructed limb from eccentric training were significantly higher than concentric training. The significant improvement was similarly demonstrated in the limb symmetry index (LSI) in hamstrings (p = 0.016) of the ACL-reconstructed limb from eccentric training. Moreover, eccentric group performed significantly better in single-leg hop tests (p = 0.042). Most importantly, eccentric group have higher percentages of return-to-sport (55.6 %) than concentric group (27.8 %). Conclusion: A 6-week course of eccentric isokinetic training was more effective than concentric isokinetic training in increasing quadriceps and hamstrings strength in terms of peak torques. Importantly, the better functional performance after the eccentric isokinetic exercise account for higher return-to-sport ratio.